Peran Instagram dalam Membentuk Perilaku Konsumsi Remaja - Lukiani, Eunike Rose Mita Lukiani; Rizka, Ayu Nur; Afandi, Tjetjep Yusuf; Arifin, Zainal; Surindra, Bayu; Irmayanti, Elis; Prastyaningtyas, Efa Wahyu (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
This community service article is a follow-up to a study entitled The Relationship between Instagram and Consumptive Behavior in Economic Education Students, Universitas Nusantara PGRI Kediri. From this research, it is known that Instagram actively contributes to shaping the consumption behavior of students in economic education to be irrational (irrational). It turns out that these findings are not yet known and are not realized by adolescents. Therefore, given the large loss of irrational consumption behavior, it is necessary to provide information (socialization) about how the contribution (role) of Instagram is in shaping consumption behavior. This form of community service is in the form of information / counseling (socialization) which is carried out to the youth of Sumberejo Village.